2022
DOI: 10.33448/rsd-v11i9.32027
|View full text |Cite
|
Sign up to set email alerts
|

Silagem de palma forrageira em dieta completa

Abstract: Objetivou-se avaliar os aspectos qualitativos da silagem de palma forrageira associada à palhada do milho (PM) ou capim elefante (CE) como fonte volumosa em dieta completa. Avaliou-se duas fontes de volumosos (PM e CE) e quatro níveis de substituição do farelo de sorgo por palma forrageira (0%, 33%, 66% e 100%), com 5 repetições. A dieta contendo a PM apresentou maior teor de NDT, PB, MM, EE e CNF e menor teor de MS, FDNcp, LIG, FDNi e CHO tot. Para os níveis de substituição do farelo de sorgo pela palma forra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…The interactions showed that the DM, ash, CP, EE, NDF, iNDF, lignin, hemicellulose, CT, and NFC content of the silages are results of the chemical composition of the pigeon pea hay included in the silage of giant cactus. These results are similar to the results of Barros et al [46], Brito et al [39], Jesus et al [40], and Matias et al [47], who evaluated cactus silage with the inclusion of other plant sources with the aim of increasing the DM content and/or the nutritional composition of the silage. The pigeon pea was also studied in the improvement of sugarcane silage [19], resulting in higher levels of CP, NDF, ADF, and hemicellulose from the inclusion of this source resulting in a superior chemical composition of the silage.…”
Section: Chemical Composition Of the Silagesupporting
confidence: 90%
See 1 more Smart Citation
“…The interactions showed that the DM, ash, CP, EE, NDF, iNDF, lignin, hemicellulose, CT, and NFC content of the silages are results of the chemical composition of the pigeon pea hay included in the silage of giant cactus. These results are similar to the results of Barros et al [46], Brito et al [39], Jesus et al [40], and Matias et al [47], who evaluated cactus silage with the inclusion of other plant sources with the aim of increasing the DM content and/or the nutritional composition of the silage. The pigeon pea was also studied in the improvement of sugarcane silage [19], resulting in higher levels of CP, NDF, ADF, and hemicellulose from the inclusion of this source resulting in a superior chemical composition of the silage.…”
Section: Chemical Composition Of the Silagesupporting
confidence: 90%
“…If the DM content of the material to be ensiled is less than 28%, the probability of negative fermentation processes that result in higher effluent losses increases [38]. The use of hay to reduce effluent losses was also observed by Brito et al [39], Jesus et al [40], and Borges et al [38].…”
Section: Fermentative Parametersmentioning
confidence: 99%